IMMU-09. CONCURRENT DEXAMETHASONE LIMITS THE CLINICAL BENEFIT OF IMMUNE CHECKPOINT BLOCKADE IN GLIOBLASTOMA. (9th November 2020) - Iorgulescu, Bryan; Gokhale, Prafulla; Speranza, Maria; Eschle, Benjamin; Poitras, Michael; Wilkens, Margaret; Soroko, Kara; Chhoeu, Chhayheng; Knott, Aine; Gao, Yang; Lim-Fat, Mary Jane; Baker, Gregory; et al.
Abstract: BACKGROUND: Dexamethasone, a uniquely potent corticosteroid, is frequently administered to brain tumor patients to decrease tumor-associated edema, but limited data exist describing how dexamethasone affects the immune system systemically and intratumorally in glioblastoma patients – particularly in the context of immunotherapy. METHODS: We evaluated the dose-dependent effects of dexamethasone when administered with anti-PD-1 and/or radiotherapy in immunocompetent C57BL/6 mice with syngeneic GL261 or CT-2A glioblastoma tumors, including analyses of intracranial tumors, draining lymph nodes, and spleen. Clinically, the effect of dexamethasone on survival was additionally evaluated in 181 consecutive IDH-wildtype glioblastoma patients treated with anti-PD-(L)1, with adjustment for relevant prognostic factors. RESULTS: Despite the inherent responsiveness of GL261 to immune checkpoint blockade, concurrent dexamethasone administration with anti-PD-1 therapy decreased survival in a dose-dependent fashion and decreased survival following anti-PD-1 plus radiotherapy in both GL261 and immunoresistant CT-2A models. Dexamethasone quantitatively decreased T lymphocytes by reducing the proliferation while increasing apoptosis. Dexamethasone also decreased lymphocyte functional capacity. Myeloid and NK cell populations were also generally reduced. Thus, dexamethasone negatively affects both the adaptive and innate immune responses. As a clinical correlate, a retrospective analysis of 181 consecutive IDH-wildtype glioblastoma patients treated with PD-(L)1 blockade revealed worse survival among those on baseline dexamethasone. Upon multivariable adjustment with relevant prognostic factors, baseline dexamethasone use – regardless of dose – was the strongest predictor of poor survival (reference no dexamethasone; < 2mg HR 2.28, 95%CI=1.41–3.68, p=0.001; ≥2mg HR 1.97, 95%CI=1.27–3.07, p=0.003). CONCLUSIONS: Our preclinical and clinical data indicate that concurrent dexamethasone therapy may be detrimental to immunotherapeutic approaches for glioblastoma patients. Our preclinical analyses also suggest that dexamethasone's detrimental effects are dose-dependent, suggesting that the lowest possible dose should be used for patients when dexamethasone use is unavoidable. Careful evaluation of dexamethasone use is warranted for neuro-oncology patients undergoing immunotherapy clinical trials.